(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Osteochondral defects are caused by injury or morphological change of the cartilage due to osteoarthritis. Current clinical treatments still face enormous challenges. The field of osteochondral tissue engineering aims to provide solutions for the repair of joint damage. As articular cartilage has a complex and hierarchical structure, a monophasic material is not sufficient for osteochondral repair. Therefore, the trend moves towards multiphasic and gradient materials [1]. Our research aims to develop an additive manufacturing process for multiphasic scaffolds addressing the needs of each segment of the osteochondral area. In this study, we focus on the fabrication using direct ink writing (DIW) and characterization of subchondral bone scaffolds made of highly loaded Polycaprolactone (PCL) with different fillers, such as barium titanate (BTO) and the bioactive glass 45S5 (BG). Different compositions are used to tailor the materials’ piezoelectric, mechanical and bioresponsive properties. By adding BTO, the piezoelectric and mechanical properties of spongy bone could be achieved, while the addition of BG increased the bioactive and osteogenic potential of the composite scaffolds compared to pure PCL. In summary, these novel material compositions provide a promising approach for developing multiphasic scaffolds for osteochondral tissue engineering.